2000
DOI: 10.1002/(sici)1521-4095(200005)12:9<637::aid-adma637>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Polymer, Metal, and Hybrid Nano- and Mesotubes by Coating Degradable Polymer Template Fibers (TUFT Process)

Abstract: pected, when the nanocrystal is isolated on a substrate a Coulomb blockade behavior is observed. With a monolayer both ohmic and Coulomb blockade contributions are observed, whereas with a fcc structure a well-defined ohmic behavior is seen. ExperimentalSilver nanosized particles were synthesized using reverse micelles, as described previously [19,20]: Colloidal silver particles were prepared by mixing two reverse-micellar solutions having the same water-content (i.e., the molarThe first was made with 30 % Ag(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
105
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(112 citation statements)
references
References 0 publications
0
105
0
1
Order By: Relevance
“…[2,[11][12][13][14][15][16][17][18][19][20] These materials can have large void volumes and high internal surface areas, but the supramolecular materials often tend to collapse upon emptying the pores. Several approaches have also been presented to prepare mesoporous and macroporous materials, such as "track-etching", [4][5][6] using honeycomb structures, [27][28][29] and emptying nanostructured templates (e.g., sol-gel processing of surfactants or block copolymers, [7][8][9][10] selective degradation of material with UV exposure, [24][25][26] pyrolysis, [21][22][23]34] and selective removal of lowmolecular-weight amphiphiles (combs) from hierarchically self-assembled polymeric comb-coil supramolecules [35,36] ). Block copolymers provide ideal structures for templates, as, by a facile route, they self-assemble into various structures as a result of the repulsion between the covalently bonded blocks; examples include the spherical, cylindrical, lamellar, and gyroid structures.…”
mentioning
confidence: 99%
“…[2,[11][12][13][14][15][16][17][18][19][20] These materials can have large void volumes and high internal surface areas, but the supramolecular materials often tend to collapse upon emptying the pores. Several approaches have also been presented to prepare mesoporous and macroporous materials, such as "track-etching", [4][5][6] using honeycomb structures, [27][28][29] and emptying nanostructured templates (e.g., sol-gel processing of surfactants or block copolymers, [7][8][9][10] selective degradation of material with UV exposure, [24][25][26] pyrolysis, [21][22][23]34] and selective removal of lowmolecular-weight amphiphiles (combs) from hierarchically self-assembled polymeric comb-coil supramolecules [35,36] ). Block copolymers provide ideal structures for templates, as, by a facile route, they self-assemble into various structures as a result of the repulsion between the covalently bonded blocks; examples include the spherical, cylindrical, lamellar, and gyroid structures.…”
mentioning
confidence: 99%
“…Strong interactions at the interface between two different layers in a hybrid material can produce unexpected novel properties and can have synergetic effects [2], therefore they can be regarded as new materials due to the emergence of these new properties. Many hybrid materials have been studied such as metal-metal hybrids, metal-organic hybrids [3], inorganic semiconductors [4], inorganic-organic hybrids [5] and carbon materials [6]. The synthesis of hybrid materials has been demonstrated using several methods, including chemical vapor deposition (CVD) [7], template-assisted synthesis [8] and self-assembly methods [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PEG with a uniform and ordered chain structure is easily absorbed at the surface of metal oxide colloid [21]. When the surface of the colloid adsorbs this type of polymer, the activities of colloid greatly decrease and the growth rate of the colloids in some certain facet will be confined [22,23]. Therefore, the addition of PEG in the metal oxide colloids will modify the growth kinetics of the growing colloids, which finally, leads to anisotropic growth of the crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the addition of PEG in the metal oxide colloids will modify the growth kinetics of the growing colloids, which finally, leads to anisotropic growth of the crystals. For this reason, linear PEG has been widely used in the synthesis of a series of nanoparticulates and 1D materials in solution [22].…”
Section: Introductionmentioning
confidence: 99%